A Qualification of Methodological Naturalism: Brightman and de Vries Revisited - Kim, Junghyung (Theology and science, 2022)
In this study I analyze what Edgar Sheffield Brightman and Paul de Vries originally meant by methodological naturalism, when they first invented the term and then argue that both of them proposed a significantly qualified version of scientific naturalism over against the predominance of a reductionist version of scientific naturalism called epistemic reductionism or scientism—that is, an unjustified epistemological assumption that science is the only legitimate way to truth. In the final analysis, I propose a qualified re-definition of methodological naturalism with emphasis on the self-restricted application of the naturalistic method to natural sciences alone.